Numerical Analysis of Electric Field in Three-Electrode Corona System Containing Ionized and Non-Ionized Areas - Barciauskas, R.; Marciulionis, P.; Zebrauskas, S. (Elektronika ir Elektrotechnika, 2014)
In many corona field applications, three-electrode and multi-electrode systems with different electrode potentials are being used. Procedure and results of numerical analysis of direct current corona field in three-electrode corona system consisting of ionizing wire placed between two parallel non-ionizing electrodes is presented in this paper. Algorithm of analysis consists of two stages. Stage 1 comprises an electrostatic approach of field analysis without space charges. Result of this stage is an equation of separatrix dividing the field into 2 areas: an area of electric flux between the corona wire and one of plane electrodes, and an area occupied by the flux between the plane electrodes. Stage 2 involves numerical analysis of the field in both areas. Numerical model is based on the assumption that the space charge of corona field doesn’t change the position and shape of separatrix. Results of modelling are validated experimentally. Proposed method of analysis allows predicting the behaviour of multi-electrode corona system using finite computer resource. DOI: http://dx.doi.org/10.5755/j01.eee.20.5.7096